Role of vitamin C in reducing cardiovascular oxidative stress: An in vivo study using sepsis rat models - Raihani, Rifa; Sovira, Nora; Andid, Rusdi; Yusuf, Sulaiman; Safri, Mulya; Dimiati, Herlina; Fajri, Fauzan; Sentosa, Sukmawan F.; Hasan, Denny I. (Narra Sains Indonesia, 2025)
The aim of this study was to evaluate the effect of vitamin C on reducing cardiovascular oxidative stress in sepsis rat models. An experimental animal study with a post-test control group design was conducted at the Laboratory of Animal Research, Faculty of Veterinary Medicine, Universitas Syiah Kuala, Banda Aceh, Indonesia, from September to December 2023, using 18 male Wistar strain rats (Rattus norvegicus). Rats were divided into three groups: control (Group K), lipopolysaccharide 5 mg/kg body weight (BW) (Group L), and lipopolysaccharide 5 mg/kg BW with oral vitamin C (18 mg/day) (Group LC). Rats were euthanized after two weeks with ketamine (15–20 mg/kg intraperitoneally) and cervical dislocation. Blood samples (3 mL) and heart organs were collected. Nitric oxide (NO) levels were measured through enzyme-linked immunosorbent assay (ELISA), and cardiac muscle cells were observed using an Olympus CX21 microscope. The LC group exhibited a significantly lower mean endothelial dysfunction score than the L group (p<0.001), although no significant difference in NO levels was observed between L and LC groups (p=0.262), indicating that vitamin C did not significantly affect NO levels. This suggests that the improvement in endothelial function observed in the LC group may be mediated through mechanisms other than NO modulation. The MANOVA test revealed that vitamin C administration accounted for 84.8% of changes in endothelial function in the sepsis rat model (p<0.001). In conclusion, vitamin C confers a protective effect against severe cardiac and endothelial damage, as evidenced by the amelioration of necrosis, inflammatory cell infiltration, congestion, and vacuolization caused by lipopolysaccharide.